1998
DOI: 10.1021/ar9602462
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA, RNA, and Proteins by Circular Oligonucleotides

Abstract: IntroductionWhile the backbone organization of DNA and RNA is normally quite regular, there are many structural forms which these molecules can adapt by undergoing various secondary and tertiary helical and folded interactions, by being subjected to twisting and bending, and by interconversion between various topological and knotted variations. Probably the most common structural form of DNA in nature is a long double helix in which the ends are joined into a circle. The genomes of most lower organisms are org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 79 publications
(136 reference statements)
0
67
0
Order By: Relevance
“…They are prototype compounds for the large variety of helical systems occuring in biochemical systems, e.g., DNA, proteins, or amyloid fibrils [7,8]. The investigation of their chiral properties has received much attention [9][10][11], and only recently an unambiguous assignment of the absolute configuration of heptahelicene could be performed on the basis of VCD spectroscopy [10].…”
Section: Introductionmentioning
confidence: 99%
“…They are prototype compounds for the large variety of helical systems occuring in biochemical systems, e.g., DNA, proteins, or amyloid fibrils [7,8]. The investigation of their chiral properties has received much attention [9][10][11], and only recently an unambiguous assignment of the absolute configuration of heptahelicene could be performed on the basis of VCD spectroscopy [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, circular oligonucleotides have been the focus of some interest because of their unusual molecular recognition properties (9). They offer some improvement compared with linear oligonucleotides as tools for genetic analysis (10,11), especially as they can be efficiently amplified by rollingcircle replication (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Transcription proceeds by a ''rolling-circle'' mechanism, generating long RNA repeats encoded by the circular DNA. This rolling circle transcription (RCT) has been demonstrated for circles in the size range 18 to Ϸ110 nt, or roughly 2-10 nanometers in diameter (6,7), and the long product RNAs have been imaged under the atomic force microscope (8)(9)(10). Such DNA circles can be used to encode concatameric or self-cleaving monomeric ribozymes of the hammerhead (2), hairpin (3), and hepatitis delta motifs (4).…”
mentioning
confidence: 99%
“…ecent work has shown that very small circular singlestranded DNAs (ssDNAs) can be efficiently transcribed by phage and bacterial RNA polymerases (1)(2)(3)(4)(5)(6)(7). Transcription proceeds by a ''rolling-circle'' mechanism, generating long RNA repeats encoded by the circular DNA.…”
mentioning
confidence: 99%